SODIUM-GLUCOSE COTRANSPORTER-2 INHBITORS AND THE RISK OF EUGLYCEMIC DIABETIC KETOACIDOSIS: A NARRATIVE REVIEW - Sergejuk, Emil; Kotlarski, Wojciech; Kotlarska, Klaudia Magdalena; Mainka, Tomasz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Euglycemic diabetic ketoacidosis (EuDKA) is a rare but life-threatening metabolic complication associated with the increasing use of sodium-glucose cotransporter-2 inhibitors (SGLT2i). Due to the absence of significant hyperglycemia, clinical diagnosis is frequently delayed, necessitating a high index of suspicion among clinicians. Methods: This review synthesizes current clinical data, retrospective studies, and international guidelines regarding the pathophysiology, risk factors, and management of SGLT2i-induced euDKA. Specific focus was placed on perioperative protocols and emerging monitoring technologies. Results: Clinical data indicate that patients with euDKA often present with milder acidosis but a significantly higher incidence of hypoglycemia compared to classic DKA. Effective management requires early initiation of 5–10% glucose infusions alongside insulin therapy to safely inhibit ketogenesis. Risk factors include rigorous low-carbohydrate diets, infection, and major surgery, with some data suggesting that up to 22% of cases initially diagnosed as type 2 diabetes are subsequently reclassified as LADA or type 1 diabetes. Continuous ketone monitoring emerges as a promising tool for early metabolic decompensation detection. Conclusion: Therapeutic success in euDKA depends on a multidisciplinary approach and rigorous adherence to preventive measures. Key strategies include the discontinuation of SGLT2i 3 to 4 days prior to elective procedures and comprehensive patient education regarding "sick day" rules and hydration.